2020
DOI: 10.3390/toxics8040090
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Maternal Cadmium Exposure with Risk of Preterm Birth and Low Birth Weight: Effect of Mediterranean Diet Adherence on Affected Prenatal Outcomes

Abstract: Prenatal cadmium exposure at non-occupational levels has been associated with poor birth outcomes. The intake of essential metals, such as iron and selenium, may mitigate cadmium exposure effects. However, at high levels, these metals can be toxic. The role of dietary patterns rich in these metals is less studied. We used a linear and logistic regression in a cohort of 185 mother–infant pairs to assess if a Mediterranean diet pattern during pregnancy modified the associations between prenatal cadmium exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The toxic effects from Cd, such as high oxidative stress, cytotoxicity and apoptosis have also been shown in humans (87). Prenatal exposure has been linked with lower birth weights, preterm deliveries and even possible spontaneous abortion (88)(89)(90). Elevated amniotic fluid levels have been also linked with pre-eclampsia (26,91).…”
Section: Discussionmentioning
confidence: 99%
“…The toxic effects from Cd, such as high oxidative stress, cytotoxicity and apoptosis have also been shown in humans (87). Prenatal exposure has been linked with lower birth weights, preterm deliveries and even possible spontaneous abortion (88)(89)(90). Elevated amniotic fluid levels have been also linked with pre-eclampsia (26,91).…”
Section: Discussionmentioning
confidence: 99%
“…It would be intriguing to observe some of their other health benefits in clinical settings. Specifically, an initial study has been reported on a cohort of 185 mother-infant pairs to assess whether a Mediterranean diet during pregnancy may modify the birth outcome of prenatal cadmium exposure at non-occupational levels [126]. Although larger trial may be necessary to elucidate their roles, it is a positive step towards our current understanding in the field.…”
Section: Conclusion and Future Researchmentioning
confidence: 99%
“…The chemical compositions of clay minerals include many potentially toxic elements (PTEs) in significantly different concentrations [5][6][7][8]. Some of these elements have harmful effects, such as As, Cd, Co, Cr, Ni, Pb, and V. Excessive exposure to these PTEs could lead to one disease or another [9][10][11][12][13][14]. Thus, it is necessary to assess the concentrations of PTEs in clay using validated quantitative and qualitative techniques, before their usage in any pharmaceutical applications [3,5].…”
Section: Introductionmentioning
confidence: 99%